Agility in Islamic Education: Adapting to Social and Technological Changes in the VUCA Era - Abdul Kodir Nurhasan; Muhammad Rizal; Syaeful Rokhman; Andika Hariyanto Surbakti; Lilis Karlina (Managere: Indonesian Journal of Educational Management, 2025)
This study examines the agility of Islamic educational institutions in adapting to social and technological changes in the VUCA (volatile, uncertain, complex, ambiguous) era. With the rapid advancement of digital technology and the increasing complexity of global challenges, educational institutions must innovate and remain flexible to remain relevant and effective in delivering education. This research examines how Nurul Jadid University has adopted international collaboration, digital transformation, and entrepreneurial innovation as strategies to meet these challenges. This study highlights initiatives through a case study approach, including organizing international conferences, collaborating with the National Library of Indonesia (Perpusnas) to modernize libraries, and launching entrepreneurship clubs to prepare students for the digital economy. The research findings show that these initiatives have an important role in equipping students with the necessary skills to deal with global market uncertainty. This research emphasizes the importance of innovation and sustainable adaptation in educational institutions and provides a model for other universities to respond to the challenges of the VUCA world. This study contributes to a broader understanding of how educational institutions can maintain relevance and effectiveness in an increasingly complex and unpredictable environment.